PVC film coatings promote post-harvest conservation of Italian zucchini fruits (Cucurbita pepo L.) (Research, Society and Development, 2020)
We evaluated the influence of storage conditions on the postharvest life of Italian zucchini fruits. Zucchinis with and without PVC coating film were evaluated at storage temperatures of 10 and 25 ºC. Evaluations were carried out at 0, 5, 10, 15 and 20 consecutive days. Zucchinis packed with PVC film at 10 ° C showed the lowest losses of fresh mass (0.84%), being the most efficient condition in reducing mass loss and maintaining the good aspects of the fruits. The treatments using 10ºC resulted in less loss of fruit firmness, regardless of packaging.  Packaging with PVC at 25 ºC presented the lowest solids content at 20 days and increments up to 15 days of tritatable total acidity, with a subsequent decline at 20 days. Tritatable acidity increased until the end of the storage period in fruits without packaging. We found a variable pH in fruits without packing and a pH reduction in fruits with PCV packing regardless of temperature. Fruits stored at 10ºC with or without packing showed smaller biomass loss. Storing Italian zucchini fruits at low temperature or coated with PVC at low temperature decrease the activity of the enzymes of solubilization of the wall components, maintaining the turgor of the tissues and extending their useful life.